Differences in vegetation characteristics with shoreline position on a tropical pocket beach. (3rd July 2020) - Grafals-Soto, Rosana; Nordstrom, Karl F.; Jackson, Nancy L.
ABSTRACT: Composition and richness of coastal vegetation differs with distance from the water and sheltering by topography. Transition from pioneer beach plants to mature forests is expected to be narrow on low wave energy coasts with a tropical climate favorable to vegetation growth. The goal of this paper is to determine whether vegetation on the beach and foredune will be denser and have a greater number of species and more woody shrubs near the water as wave and wind stresses diminish because of favorable shoreline orientation within a pocket beach. Field data on beach width, beach mobility, dune height, vegetation species, vegetation height and percent vegetation cover were collected in Puerto Rico along six cross-shore transects. Beaches are more stable at transects in the lee of an eolianite barrier and a tombolo. The vegetation gradient there is compressed, with denser, taller, more diverse vegetation and more tree species close to the waterline than at more exposed sites. The lack of mobility of the beaches and dunes and lack of geomorphically significant disturbance events is in contrast to the conspicuous feedbacks between overwash, topography, and vegetation on exposed mid-latitude coasts, revealing the need for more study of low-energy beach environments.